Preparation Process Optimization and Its Stability of Selenium-Rice Protein Peptides Nanoparticles - Yanfang OU; Chenghua WANG (Shipin gongye ke-ji)
In this study, selenium-rice protein peptide nanoparticles were prepared using rice protein peptides as stabilizers and ascorbic acid (VC) to reduce sodium selenite (Na2SeO3), with the particle size, polydispersity index, and Zeta potential serving as indicators for evaluation. To optimize the preparation conditions, a combination of single-factor and orthogonal experiments was performed to determine the molar concentration ratio of VC to Na2SeO3, amount of rice protein peptide added, reaction time, and reaction temperature. Preliminary structural analyses of the nano-selenium were performed using scanning electron microscopy and Fourier-transform infrared spectroscopy. Additionally, the stability of the nano-selenium was investigated under different pH conditions, ion supplementation, and storage at 4 and 25 °C. The results revealed that the optimal preparation conditions were a VC:Na2SeO3 molar concentration ratio of 4:1, the addition of 5 mg/mL rice protein peptide, a reaction time of 5 h, and a reaction temperature of 25 °C. Under these optimal conditions, the average particle size, polydispersity index value, and Zeta potential value of the nano-selenium were 92.00±2.68 nm, 0.104±0.008, −37.20±2.52 mV, respectively. The selenium-rice protein peptides nanoparticles were characterized by a three-dimensional network structure with the nano-selenium particles dispersed within. The system was established to be stable under alkaline conditions, more sensitive to Ca2+ than to Na+, and remained stable for 35 days at 4 °C. The findings indicate that this material would be suitable for selenium supplementation at room temperature but not for high-temperature processing. This study provides theoretical support for the high-value utilization of rice protein resources and serve as a basis for the further research and development of selenium-rice protein peptides nanoparticles.